The Effect of the Project Based Learning (PjBL) Model on Students’ Learning Outcomes in Local Wisdom Materials in Elementary Schools - Raimon Efendi; Wiwik Okta Susilawati; Ellen Santika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study identifies a problem related to the lack of variation in the implementation of learning models, which has an impact on students’ learning achievement. Many students experience difficulties in understanding the lessons because teachers tend to focus on content delivery without considering students’ individual characteristics. In fact, the classroom consists of diverse student learning style preferences, including auditory, visual, and kinesthetic learning styles. Therefore, this study aims to investigate the effect of the Project Based Learning (PjBL) model on students’ learning outcomes in the IPAS subject, particularly on the topic of Cultural Diversity, among fourth-grade students at SDN 02 Tiumang. Through the implementation of the Project Based Learning model, a significant improvement in students’ learning outcomes is expected. This research employed a quantitative approach using an experimental method with a One-Group Pretest–Posttest Design. The research sample consisted of 14 fourth-grade students at SDN 02 Tiumang. Data collection techniques included observation, interviews, tests, and documentation. The learning model applied was Project Based Learning. The test was administered twice to determine the improvement in students’ learning outcomes before and after the treatment. Prior to classroom implementation, the test items were piloted. The instrument trial was conducted with fifth-grade students at SDN 02 Tiumang using 30 multiple-choice items, which were subsequently analyzed through validity and reliability tests. The results of the validity test showed that 25 items were valid, while 5 items were invalid. The reliability test yielded a coefficient of 0.899, indicating high reliability. Data analysis techniques included a normality test using the Shapiro–Wilk formula and hypothesis testing using a paired sample t-test. The pretest results showed an average score of 53.71, while the posttest average score increased to 83.71, indicating a significant improvement in learning outcomes. The paired sample t-test analysis resulted in a calculated t-value (tₕᵢₜᵤₙg) of 11.208, while the t-table value with degrees of freedom (n–1) = 13 at a 5% significance level was 0.514. Thus, tₕᵢₜᵤₙg > tₜₐᵦₗₑ (11.208 > 0.514), indicating that Ha is accepted and H₀ is rejected.